The PoSE Project: the Potential of Technological Learning for Postural Education in Schoolchildren - Ilaria Bortone; Nadia Agnello; Alberto Argentiero; Valentina Denetto; Cosimo Neglia; Giuseppe Palestra; Marco Benvenuto (European Alliance for Innovation (EAI), 2015)
Back pain in children and adolescents is quite common, so developing preventive strategies for back pain is highly desirable. This article describes a planned school-based postural education project (PoSE) to promote healthy behaviors among middle school students and their families and to moderate postural diseases. As first s tep, we e valuated which a spects of postural behaviors were integrated in children's lifestyle through a questionnaire. Then, the educational program consisted of interactive lessons on back posture and good principles both in class and at home. A participatory approach was used to evaluate attempts to involve all who have a stake in outcomes in order to take action and effect change. The strength of the participatory approach used in this study lies in the contribution to empowerment social change.